Raleigh's page - Armstrong, Alan W. (Childrens books, 2007)
In the late 16th century, fifteen-year-old Andrew leaves school in England and must prove himself as a page to Sir Walter Raleigh before embarking for Virginia, where he helps to establish relations with the Indians.